2010
DOI: 10.1590/s0100-72032010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Homocisteinemia em mulheres com síndrome dos ovários policísticos

Abstract: dilênia de oliVeira Cipriano torres 5 ana Célia oliVeira dos santos 6 Artigo originalResumo OBJETIVOS: comparar os níveis sanguíneos de homocisteína em mulheres com e sem a síndrome dos ovários policísticos (SOP) e correlacioná-los com os parâmetros clínicos, hormonais e metabólicos. MÉTODOS: estudo tipo corte transversal com 110 mulheres: 56 com SOP e 54 controles normais. As pacientes foram submetidas à anamnese, exame físico e ultrassonografia pélvica, dosagens de homocisteína, da proteína C reativa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…We found significant changes in the concentrations of FPI, FPG, LH, and FSH among the newly diagnosed POCS women compared with the controls and the treated group. Some previous studies also showed clear differences in hormonal and metabolic parameters between non-PCOS and PCOS women [11][12][13][14] . Since insulin resistance is common in women with PCOS and is believed to be a key factor in the pathogenesis of PCOS 15 , we calculated HOMA-IR to assess the effect of PCOS on insulin sensitivity among all participants.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found significant changes in the concentrations of FPI, FPG, LH, and FSH among the newly diagnosed POCS women compared with the controls and the treated group. Some previous studies also showed clear differences in hormonal and metabolic parameters between non-PCOS and PCOS women [11][12][13][14] . Since insulin resistance is common in women with PCOS and is believed to be a key factor in the pathogenesis of PCOS 15 , we calculated HOMA-IR to assess the effect of PCOS on insulin sensitivity among all participants.…”
Section: Discussionmentioning
confidence: 77%
“…The study found that the levels of FPG and HOMA-IR were significantly higher in PCOS Brazilian women compared to healthy controls 16 . Another study carried out in 2010 showed significant differences in insulin concentration and HOMA-IR between the PCOS group and non-PCOS controls 11 . Interestingly, we found that no valuable changes between the treated PCOS women and controls in the levels of FPI, FPG, LH and FSH, as well as HOMA-IR.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the glucose profile, the mean Hy value was higher in patients with elevated fasting insulin and / or insulin resistance. Studies have shown that elevated plasma insulin levels can lead to Hhe, possibly due to changes in enzymes involved in the Hy metabolism, especially cystathionine-β-synthase, involved in the transsulfuration pathway [35] [36].…”
Section: Discussionmentioning
confidence: 99%
“…Cerqueira et al (2010) também demostraram resultados semelhantes ao estudo, onde os níveis de LH e testosterona foram significativamente mais elevados no grupo SOP em relação ao grupo controle. Em relação ao estilo de vida, sobressaíram, na maioria dos grupos avaliados, mulheres que não consomem álcool, tabaco e são sedentárias.…”
unclassified